Evolution of the biomechanical dimension of the professional gestures of grinders when using a collaborative robot. Issue 2 (3rd April 2023) - Schoose, C.; Cuny-Guerrier, A.; Caroly, S.; Claudon, L.; Wild, P.; Savescu, A.
ABSTRACT: Using a cobot could relieve workers of strenuous and repetitive tasks while preserving their expertise. To understand the consequences of using a cobot on the occurrence of musculoskeletal disorders (MSDs), within a theoretical framework based on activity-centred ergonomics, an example cobot used in grinding activities in a real work situation is studied. This article analyses the evolution of the biomechanical dimension of the professional gestures of grinders when using the cobot. Effort linked to tool carrying and the vibrations perceived were reduced. Repetitiveness decreased but workers did not accomplish the entirety of their task. The work postures did improve for different joints but not for all, which shows the advantage of varying the contexts of using a cobot and taking into account workers' strategy diversity. To investigate other explanatory elements of the effects on MSDs, these results must be linked to the evolution of the other dimensions of professional gestures.